Vogt–Koyanagi–Harada Syndrome in a Ugandan: Diagnostic and Therapeutic Challenges - Felix Bongomin; Francis S. Onen; Mark Kaddumukasa (Case Reports in Medicine)
Background. Vogt–Koyanagi–Harada (VKH) syndrome is a multisystemic autoimmune disease of uncertain pathogenesis. Infectious aetiology has been proposed which is suggested to lead to the loss of melanocytes in the skin, inner ear, meninges, and uvea in those who are genetically predisposed. Information regarding VKH syndrome is scanty among the African population. Case Presentation. We report a 28-year-old HIV-uninfected Ugandan woman who had previously been well and presented with chronic bilateral panuveitis; symmetrical vitiligo patches on the head, trunk, and upper limbs; tinnitus; and poliosis of the scalp hair, eyelashes, and eyebrows. A flu-like syndrome preceded this. Several weeks of prednisolone and azathioprine therapy resulted in remarkable improvement of the ocular and inner ear symptoms. Conclusion. A high index of suspicion is required in diagnosing VKH syndrome, even in sub-Saharan Africa where the disease is reported to be rare. Initiation of prompt and appropriate treatment prevents blindness and other complications.